Early mover advantage in Roundtable on Sustainable Palm Oil certification: a panel evidence of plantation companies - Tey, Yeong Sheng; Brindal, Mark; Darham, Suryani; Sidique, Shaufique Fahmi; Djama, Marcel (Elsevier, 2020)
The adoption of sustainable palm oil standards remains voluntary. It is unclear whether early adopters achieve better financial performance than those who lag in adopting. This study examines how the profitability, in terms of the return on invested capital (ROIC) of plantation companies is impacted by the entry order of the adoption of the Roundtable on Sustainable Palm Oil (RSPO) sustainability standard. Based on the 2000–2016 panel data of the 39 plantation companies listed on the Kuala Lumpur Stock Exchange, this study has demonstrated profitability as being influenced by the timing of entry (adoption), related resource allocation, business efficiency, and the price of crude palm oil. Since early adopters (plantation companies) realised a positive relationship with ROIC, the presence of an early mover advantage can be hypothesised. This positional advantage is likely to yield both operating and capital efficiencies, such as those predicated in the good management practices of the RSPO standard. This finding is useful as a motivational strategy to augment the acceptance of international palm oil standards among plantation companies, which are often a nucleus to smallholders. The implications for firms adopting other sustainability standards are also discussed.